(untitled) (Jurnal Geomine, 2019)
The increasing development of the mining industry carries the risk of environmental pollution and damage. PT. Vale Indonesia Tbk. is one of the nickel mining companies in South Sulawesi Province. Mining activities of PT. Vale Indonesia Tbk. produce waste water contaminated with Cr6+ with the concentration of 0.56 ppm which is not in accordance with the quality standards of nickel mining wastewater listed in PERMENLH No.9/2006, then the necessary treatment is next. This study tried to use the phytoremediation method with phase growth parameters of water hyacinth plants against phytoremediation of Cr6+ and knowing pH absorption. In this study 3 treatments were carried out on wastewater, including treatment of one wastewater with water hyacinth phase growing young with plant height <35 cm, treatment of two wastewater with medium-growth water hyacinth with a plant height of 35-60 cm, and treatment of 3 water waste with old water hyacinth grows with a plant height of 60-80 cm, with a phytoremediation time of 7 days. Water hyacinth plants are taken from the waters of the Makassar Jeneberang River by purposifemethod sampling. For analysis of metal content of Cr6+ usedmethod UV Spectrophotometry based on SNI 6989.71.2009 in Water and Environmental Laboratories of the Center for Estate Crops Industry. The results showed that phytoremediation of Cr6+ by water hyacinth plants was able to reduce Cr6+ to reach a concentration of 0.2050 ppm carried out by medium phase water hyacinth plants, with the best absorption occurring on the first day. As well as water hyacinth plants for all phases can reduce the pH value of water towards a more neutral value.